Immunogenicity and protective efficacy of nanoparticle formulations of L-SseB against Salmonella infection - Das, Sayan; Howlader, Debaki R.; Lu, Ti; Whittier, Sean K.; Hu, Gang; Sharma, Simran; Dietz, Zackary K.; Ratnakaram, Siva S. K.; Varisco, David J.; Ernst, Robert K.; Picking, William D.; Picking, Wendy L. (Frontiers in Immunology, 2023)
Salmonella enterica, a Gram-negative pathogen, has over 2500 serovars that infect a wide range of hosts. In humans, S. enterica causes typhoid or gastroenteritis and is a major public health concern. In this study, SseB (the tip protein of the Salmonella pathogenicity island 2 type III secretion system) was fused with the LTA1 subunit of labile-toxin from enterotoxigenic E. coli to make the self-adjuvanting antigen L-SseB. Two unique nanoparticle formulations were developed to allow multimeric presentation of L-SseB. Mice were vaccinated with these formulations and protective efficacy determined via challenging the mice with S. enterica serovars. The polysaccharide (chitosan) formulation was found to elicit better protection when compared to the squalene nanoemulsion. When the polysaccharide formulation was used to vaccinate rabbits, protection from S. enterica challenge was elicited. In summary, L-SseB in a particulate polysaccharide formulation appears to be an attractive candidate vaccine capable of broad protection against S. enterica.